Liquid biopsies. Issue 4 (8th February 2019) - Lianidou, Evi; Pantel, Klaus
Abstract: Liquid biopsy is based on minimally invasive blood tests and has a high potential to significantly change the therapeutic strategy in cancer patients, providing an extremely powerful and reliable noninvasive clinical tool for the individual molecular profiling of patients in real time. Liquid biopsy approaches include the analysis of circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), circulating miRNAs, and tumor‐derived extracellular vesicles (EVs) that are shed from primary tumors and their metastatic sites into peripheral blood. The major advantage of liquid biopsy analysis is that it is minimally invasive, and can be serially repeated, thus allowing extracting information from the tumor in real time. Moreover, the identification of predictive biomarkers in peripheral blood that can monitor response to therapy in real time holds a very strong potential for novel approaches in the therapeutic management of cancer patients. In this review, we summarize recent knowledge on CTCs and ctDNA and discuss future trends in the field.